2014
DOI: 10.1108/imefm-01-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance of Islamic banks

Abstract: Purpose – This paper aims to understand the current governance practices and governance structure of Islamic banks (IBs) in Gulf Cooperation Council (GCC) and Southeast Asia countries with the purpose of providing relevant information in guiding the future development of the governance system for IBs. As well, the paper discusses and compares the state of the governance system in GCC countries (Kuwait, Bahrain, United Arab Emirates, Qatar and Saudi Arabia) and Southeast Asia countries (Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 8 publications
4
53
1
2
Order By: Relevance
“…The DPS is also motivated religiously to comply with the function regarding the pursuit of meliorating the efficiency of Sharia banks (Pfeffer & Salancik, 1978). Overall, DPS has high influence on decision making regarding Islamic banks' risk (Farag, Mallin, & Ow-Yong, 2018;Grassa & Matoussi, 2014). and Mollah & Zaman (2015) found that a larger DPS size may lower Islamic banks' risk due to increased oversight ability.…”
Section: Do Corporate and Sharia Compliance Governance Affect Enterprmentioning
confidence: 99%
See 2 more Smart Citations
“…The DPS is also motivated religiously to comply with the function regarding the pursuit of meliorating the efficiency of Sharia banks (Pfeffer & Salancik, 1978). Overall, DPS has high influence on decision making regarding Islamic banks' risk (Farag, Mallin, & Ow-Yong, 2018;Grassa & Matoussi, 2014). and Mollah & Zaman (2015) found that a larger DPS size may lower Islamic banks' risk due to increased oversight ability.…”
Section: Do Corporate and Sharia Compliance Governance Affect Enterprmentioning
confidence: 99%
“…Withal, one of the five pillars of good corporate governance is transparency (Magalhães & Al-Saad, 2013). Transparency of a company can be measured from its disclosure, hence the ERM disclosures are expected to help build a strong governance framework (Grassa & Matoussi, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings indicate that role of the Sharia Board in Malaysia and Indonesia do not differ significantly from one another if legislative, business environment conditions and proactive government role are not factored. Grassa and Matoussi (2014) in their paper on "Corporate governance of Islamic banks: A comparative study between GCC and Southeast Asia countries", compared the governance system in GCC countries and Southeast Asia countries using a sample of 83 Islamic banks across four variable -ownership structure, board of directors, Shariah board and CEO attributes. Their study found significant differences in corporate governance structure of IBs in GCC countries and the Southeast Asia countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several researchers have highlighted the difference between conventional and Shari'ah governance. According to Grassa and Matoussi (2014) the governance practices in IFIs must be found in Shari'ah law. Ahmad and Chapra (2002) mentioned that Shari'ah governance emphasises on fairness to all stakeholders by enhancing transparency and accountability which are in line with the teachings of the Shari'ah.…”
Section: Shari'ah Governancementioning
confidence: 99%